Lateral flow assays for diagnosing invasive pulmonary aspergillosis in adult hematology patients: A comparative multicenter study. (9th July 2019) - Mercier, Toine; Dunbar, Albert; de Kort, Elizabeth; Schauwvlieghe, Alexander; Reynders, Marijke; Guldentops, Ellen; Blijlevens, Nicole M A; Vonk, Alieke G; Rijnders, Bart; Verweij, Paul E; Lagrou, Katrien; Maertens, Johan
Abstract: Fast diagnosis of invasive pulmonary aspergillosis (IPA) is essential as early adequate therapy improves survival. However, current microbiological methods suffer from a low sensitivity or a long turnaround time, often as a result of batching. Recently, two lateral flow assays for diagnosing IPA have been CE (Conformité Européenne)-marked and commercialized. These assays can be used for fast single sample testing. However, clinical validation and comparative studies are lacking. We therefore sought to evaluate and compare these assays in adult hematology patients. We retrospectively tested 235 bronchoalveolar lavage fluid (BALf) samples of adult hematology patients from four centers using the AspLFD (OLM Diagnostics) and the sōna Aspergillus galactomannan LFA (IMMY). Both tests were read out independently by two researchers and by a digital reader. We included 11 patients with proven IPA, 64 with probable IPA, 43 with possible fungal disease, and 117 controls with no signs of IPA. In cases of proven IPA, the performance of both assays was similar. In cases of proven and probable IPA, we found an identical specificity for both assays, but a higher sensitivity (0.83 vs 0.69, P = .008) and a better negative predictive value (0.89 vs 0.82, P = .009) for the LFA. Digital readout improved the diagnostic performance of both tests. In conclusion, both assays showed a good performance for the diagnosis of IPA in BALf from adult hematology patients. Results were further improved by using a digital reader, especially for weakly positive results.